Recurrence and outcomes of non‐functional pancreatic neuroendocrine tumours post‐resection: an Australian retrospective, multicentre cohort study. Issue 1 (22nd December 2022) - Lim, Sean; Chong, Lynn; Peeroo, Saania; Onasanya, Olukunle; He, Evelyn; Banting, Simon; Croagh, Daniel
Abstract: Introduction: Pancreatic neuroendocrine tumours (PNETs) are heterogenous entities with variable clinical outlook. The prevalence of PNETs is increasing in Australia. Despite this, data on peri‐operative management and post‐operative prognosis for Australian patients is scant in the literature. Methods: Patients from two tertiary hospitals in Victoria were recruited. Inclusion criteria included patients who underwent curative surgical resection for primary, non‐functioning, PNETs without metastases from January 2011 to December 2021. Patients were identified via histopathological reports, CMBS and ICD‐10 codes. Data were sourced from Electronic Medical Records, outpatient notes and letters. Results: Sixty‐three patients (34 Male, 29 Female) underwent surgical resection for PNETs. Fifty‐three patients (84.1%) had a post‐operative complication, and 21 (33.3%) had severe complications. Two patients had disease recurrence. Head PNETs had higher Ki‐67% (5.33 vs. 2.72, P = 0.29), and likelihood of nodal spread (9 (36%) vs. 4 (16%), P = 0.054). Pancreatic Head resections were also associated with more frequent ICU admissions (21 (84%) vs. 18 (54.5), P = 0.024), longer ICU stays (4.05 vs. 2.17 days, P = 0.10) and hospital stays (26.76 vs. 8.27 days, P = <0.001). Conclusion: Within the limitations of this study, it demonstrates that surgical resection of PNET carries a significant morbidity with a low rate of recurrence. Additionally, Pancreatic head NETs may be associated with higher grades and increased likelihood of nodal metastases. Considering this, careful patient selection is paramount. Abstract : The prevalence of PNETs (Pancreatic Neuroendocrine Tumours) is increasing in Australia. Despite this, data on peri‐operative management and post‐operative prognosis for Australian patients is scant in the literature. This study characterises the work‐up, management, and outcomes of surgically resected PNETs in Australia in comparison to other countries. Within the Australian population, resection of PNETs carries significant morbidity with low rates of post‐operative recurrence.